The Ills of Domestic Violence in a Nigerian Family (Global Journal of Human-Social Science, 2020)
The study investigated the effects of domestic violence on family development and growth in the Nigerian society. States in the Niger Delta Region were selected for the study. Domestic violence ranging among others had been plaguing the fabric of the Nigerian society of late. Researchers, in their findings, have come up with different results, which are mostly the negative effect domestic violence created on the family growth, development, family income, and the position of the relevant legal system. The objectives of the study are to examine the effect of domestic violence on family growth, to probe the impact of domestic violence on the development of domestic family, how the family income is affected by domestic violence, and the role of the legal system in curbing frequent occurrences. The research adopted a survey method. A questionnaire was distributed to gather data for analysis. The population size of 360 was got from the nine states in the Niger Delta Region. Data were collected and analysed using Chi-Square Statistical Method. The result showed that domestic violence has a significant relationship on family development and growth and the legal system in the study area.
Keywords: domestic violence; family growth and development; niger delta region; nigerian society